Goats Market Efficiency in Darfur Region: A co-Integration Analytical Approach - F. Mohamed, ElAgib; A. Mohamed, Dawelbiet (المجلة الزراعية; مجلد 2 عدد 2 (2004), 2021)
The objective of this study is to understand the nature of the market efficiency for goats market in Darfur region. The study was based on weekly prices of goats in six market locations, namely, Nyala, Elfashir, Umkaddada, Kutum, Mellit and Elgeneina during the period of the first week of January 1998 to the last week of March 2003. The co-integration regression analysis revealed all markets are spatially integrated and there is stable equilibrium relationship between markets, i.e. highly. co-integrated. This implies that commodity arbitrage .is working and the markets are efficient. Therefore, the study concluded that price changes in the selected markets reflect the state of market performance. This study demonstrated the importance of having reliable and timely market information for policy makers, traders, and farmers to make informed decisions.